An Ordered Logit Model for Predicting Corporate Sukuk Ratings in Malaysia and Indonesia - Nurhanifah, Afifa; Tazliqoh, Agustifa Zea; Rika Nur Ismawati (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This research aims to examine the association accounting information quality (accrual quality and cash flow management), corporate governance, sukuk structures, and guarantee status to affects corporation sukuk rating. This research used criteria and methodology general approach sukuk rating published by sukuk rating agency such as PEFINDO, RAM and MARC. Using sukuk rating as dependent variable, ordered logit model is selected to test research variable. This research finds that accrual quality, sukuk structure, status guarantee, and firm size positively associated with sukuk rating. However, profitability, leverage, and growth variables were not have associated with sukuk rating.